Chibi manga : irresistible! - Minguet, Eva (Harper Design, an imprint of HarperCollins Publishers, 2016)
The most complete how-to-draw book on this manga style, Chibi Manga covers both manga and anime, and includes detailed information on how to apply digital color, 3D designs, vectorial drawing, and a host of other fascinating and useful design applications to go from initial black-and-white sketches to vibrant, fully costumed collections. Each project in this easy-to-follow guide includes precise step-by-step instructions, a list of specific software, tools, and professional tricks to achieve the unique look and mischievous quality of these adorable characters and animals.